Credit and Private Equity Financing in Young Innovative Small and Medium-sized Companies in Germany - Dorothea Schäfer; Axel Werwatz; Volker Zimmermann (Weekly Report, 2005)
Successful newly established companies are a significant factor for the prosperous development of a national economy. Young innovative companies play a key role in the quick market launch and distribution of new technologies and products. As founders only rarely have sufficient own funds, financing has a considerable influence on the success of a newly established company. In the course of the investment boom in the USA and the breathtaking speed at which American Venture Capital (VC) companies listed their newly established portfolio companies in the stock market, the general attitude seems to be that a strong VC sector makes a significant contribution to the establishment of new companies and to innovation. However, it remains to be seen what role banks play in financing young technology companies. The analysis conducted by DIW together with the KfW bank group concerning the financing pattern of credit institutions and private equity companies in the sector of young technology companies is an initial contribution towards closing the gap in regard to the German market.1 The result of the analysis2 is that private equity is very likely to flow into investments bearing a higher financial risk. However, such clear statements cannot be made in connection with the economic performance risk _ possibly expressed in terms of innovation contents and objectives of the project. Many indicators for the economic performance risk _ this includes the company's R&D-orientation as well as various characteristics of the executed innovation projects _ proved to be insignificant or do not show the expected trend. Only the variable 'regular research and development' increases the likelihood of receiving private equity financing. The next step in the course of the research cooperation between DIW Berlin and the KfW bank group will be the quest for the causes of these unexpected findings.
Keywords: 330